Head Trauma in Children: An Epidemiological Study - Badebarin, Davoud; Aslan Abadi, Saeed; Farhadi, Ebrahim; Ladan, Amir Hossein; Mousavi Toomatari, Seyed Ehsan (Iranian Journal of Pediatric Surgery, 2021)
Introduction: Brain injury is one of the most common causes of death among victims of trauma in various accidents. The type of accident and outcome could be different in children from adults. Therefore, we aimed to investigate the epidemiology of traumatic head injury in children. Materials and Methods: In this cross-sectional study, 114 patients (age≤15 years) with head trauma, who were admitted to trauma ward of Imam Reza hospital in 2018 were enrolled in the study. Data regarding the demographic characteristics, mechanism of trauma, season of trauma, hemodynamic findings and outcome of the patients were collected. Results: The mean age amongst victims of trauma was 6.52±3.95 years and majority of them (70.2%) were male. Most of traumatic accidents took place in the spring (27.2%) and summer (32.5%). Traffic accidents (pedestrians or passenger) (55.3%) and falling (39.5%) were the most common mechanism of trauma. Also, epidural hematoma (EDH) and brain contusion were the most encountered type of brain injury (1.75%). Nine patients (7.89%) underwent brain surgery. Eventually, eight patients (7.17%) died. Conclusion: Falling and vehicle accidents are the main causes of head injury among children. Increasing the parents’ awareness toward these types of accidents and proper preventive measures can reduce traumatic brain injury.